SKETSA SOSIOGRAFI MASYARAKAT ISLAM DI INDONESIA - Yuli Umro'atin; M. Zaki Suaidi (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
A long with the development, many problems of the people that arose that did not exist at the time of the Prophet SAW. This problems require precise and fast solution. One of the media for solving it is through the method of tajdid and ijtihad. Tajdid seeks to restore Islamic teachings that have been forgetten or abandoned by Muslims and then reformed in a better direction. Deviance for Sosiolog with give a expectation promise for the peoples. The Sosiologs very get to know the condition of peoples with a social phenomenon indiced by them. This research with a Library Research that data evidence procces does by the written this research and get by study library and books. The result of this research are: The muslim problems now, the problems in the reformation era at temporary development or knowledge development and sains technology, low quality of public morality and human character quality in Indonesia. The profil of muslim society now are the positive and negative character, the positive character are historis muslim society, normative muslim society, and culture. Negative character are many the comprehension of mistake religious, much the beliefe deviation, morals, Islam low, and ideology deviation.